1993
DOI: 10.1128/jb.175.15.4895-4904.1993
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic identification and phylogenetic analysis of the spotted fever group rickettsiae by pulsed-field gel electrophoresis

Abstract: Using pulsed-field gel electrophoresis, we studied the chromosomes of spotted fever group rickettsiae. We digested the DNA of 16 species currently known to belong to this group with SmaI, EagI, and BssHII. The genome size of 13 rickettsiae was between 1,200 and 1,300 kb. "Ricketisia massiliae" and "R. helvetica" genome sizes were 1,370 and 1,397 kb, respectively, and that ofR. bellii was 1,660 kb. It was possible to obtain distinctive patterns for each species, but in R. conorii, 10 isolates exhibited the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
65
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 47 publications
9
65
0
2
Order By: Relevance
“…Thereafter, the purified organisms were washed in PBS (three times for 10 rnin each time at 17,500 X g) and resuspended in distilled water at a concentration of 1 mg/ml (Total Protein Test; Bio-Rad Laboratories, Richmond, Calif.) for SDS-PAGE and Western blotting. Purification of rickettsiae for PFGE was carried out by following the same procedure, but K36 buffer (16.5 mM KH,PO,, 33.5 mM K2HP0,, 100 mM KC1, 15.5 mM NaC1) was used instead of PBS and distilled water (36). The material collected in a further flask was frozen at -80°C until required for mouse immunization, serologic typing, PCR-RFLP analysis, or nucleotide sequence determination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, the purified organisms were washed in PBS (three times for 10 rnin each time at 17,500 X g) and resuspended in distilled water at a concentration of 1 mg/ml (Total Protein Test; Bio-Rad Laboratories, Richmond, Calif.) for SDS-PAGE and Western blotting. Purification of rickettsiae for PFGE was carried out by following the same procedure, but K36 buffer (16.5 mM KH,PO,, 33.5 mM K2HP0,, 100 mM KC1, 15.5 mM NaC1) was used instead of PBS and distilled water (36). The material collected in a further flask was frozen at -80°C until required for mouse immunization, serologic typing, PCR-RFLP analysis, or nucleotide sequence determination.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the bacterial suspensions of MC16T, R. massiliae (type strain MtulT and strain GS), R. rhipicephali, and Bar29 was added to 1 volume of Incert Agarose (FMC Bioproducts, Rockland, Maine) to form agarose blocks and lysed as previously reported (36). The plugs were digested with the endonucleases SmaI (Boehringer-Mannheim), EagI (New England BioLabs, Beverly, Mass.…”
Section: Sds-page and Western Blot Immunoassaymentioning
confidence: 99%
“…When the citrate synthase gene amplified material was digested by AluI, it produced a unique profile. The migration patterns for the genome of strain MtulT digested with different enzymes (SmaI, EagI, and BssHII) and analyzed by pulsed-field electrophoresis were clearly different from the profiles obtained for the reference SFG rickettsiae Therefore, strain MtulT can be considered a new species distinct from all previously recognized SFG rickettsiae, not only on the basis of the usual serological criteria, but also on the basis of the results of two different genetic analyses (3,4,8). The polymerase chain reaction-restriction fragment length polymorphism profile of MtulT, obtained after amplification of the citrate synthase gene and digestion with AluI, is unique and distinct from the profile found for all previously described SFG rickettsiae.…”
mentioning
confidence: 99%
“…Gimenez-stained infected cells contain small, intracellular, rod-shaped or diplobacillary bacteria that are slightly shorter (0.3 to 0.4 by 0.6 to 1 pm) than the other SFG rickettsiae (3). This organism can also be detected in infected cells by indirect immunofluorescence by using human immune sera reactive with the lipopolysaccharide of Rickettsia cunurii, a cross- (8).…”
mentioning
confidence: 99%
“…Using the 16s and 23s rRNA gene sequences, we determined that R. bellii is the product of an early divergence which occurred prior to the schism between the SFG and TG. While some other workers have suggested that this species should occupy a peripheral position (10,26,27), we describe the first quantitative classification of R. bellii in which genes with known evolutionary patterns were used. In addition, our data provide insight into more extensive proteobacterial comparisons; they indicate that the genus Rickettsia is a distinct, ancient lineage of the 01 subgroup of the Proteobacteria.…”
mentioning
confidence: 99%